2016
DOI: 10.17221/131/2015-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Profitability development of Czech dairy farms

Abstract: Th e paper deals with the development and main determinants of the profi tability of Czech dairy farms. Th e aim of the paper is to evaluate the diff erences in the dynamics of profi tability for two types of milk producers -specialized dairy farms and mixed farms -within the context of the agricultural policy changes. Th is aim is achieved by decomposing profi tability into output growth, output and input price changes, changes in decoupled subsidies, technical change, scale, mark-up, and technical effi cienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…The profitability of dairy farms can be improved by new technologies, better nutrition, herd management and advances in genetics (Stelwagen et al, 2013). It is recognized that the old EU members have more specialized dairy farms and their share is about 95% (Kroupova, 2016). The economic development of dairy farms can be measured by the total standard output (SO -SE005=total standard output in €/1 000).…”
Section: Characteristics Of Dairy Farms In the Eumentioning
confidence: 99%
See 1 more Smart Citation
“…The profitability of dairy farms can be improved by new technologies, better nutrition, herd management and advances in genetics (Stelwagen et al, 2013). It is recognized that the old EU members have more specialized dairy farms and their share is about 95% (Kroupova, 2016). The economic development of dairy farms can be measured by the total standard output (SO -SE005=total standard output in €/1 000).…”
Section: Characteristics Of Dairy Farms In the Eumentioning
confidence: 99%
“…Our analysis confirmed that dairy farms from Czech Republic gained much from their accession to the EU. According to Kroupova (2016) the new members of the EU had the growth in milk yield, the reduction in the number of cows and world market price development. As a result, the increase of milk production in specialized dairy farms has been observed.…”
Section: The Hellwig Measure Of Economic Sustainability Of Dairy Farmmentioning
confidence: 99%
“…Однак, на думку чеських науковців, технологічна ефективність не є найважливішим фактором, що визначає прибутковість. Зміна ціни впливає на зміну прибутковості значно більше (Zakova Kroupova, 2016). Ціна є також мотиваційним чинником у молочному скотарстві для фермерів (Gorbanyuk, 2018).…”
Section: таблицяunclassified
“…Solving the task of food security on a global scale requires efficient management of agribusiness in separate clusters of crops and animal husbandry [11]. Mathematical methods for improving dairy production in line with national features of activities are successfully applied in assessing the competitiveness of dairy producers in Slovakia [12], in comparing profitability of specialized dairy and mixed farms in the Czech Republic [13], in predicting wholesale and retail prices for milk in Hungary [14]. However, the current state of milk production in Ukraine and in regions leads to a conclusion that the employment of mathematical apparatus for improving management in agriculture is among the unsolved issues.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%